2014
DOI: 10.1186/1471-2199-15-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel, non-radioactive eukaryotic in vitro transcription assay for sensitive quantification of RNA polymerase II activity

Abstract: BackgroundMany studies of the eukaryotic transcription mechanism and its regulation rely on in vitro assays. Conventional RNA polymerase II transcription assays are based on radioactive labelling of the newly synthesized RNA. Due to the inefficient in vitro transcription, the detection of the RNA involving purification and gel electrophoresis is laborious and not always quantitative.ResultsHerein, we describe a new, non-radioactive, robust and reproducible eukaryotic in vitro transcription assay that has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…5c ). Moreover, we used an in vitro RNAP2-dependent run off assay to measure the de novo transcription in vitro 41 . The HeLaScribe DNA template was incubated with nuclear extracts from the isogenic DU145 cells expressing Dox-inducible RBX1 shRNAs, and a transcription reaction without nucleoside triphosphates served as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…5c ). Moreover, we used an in vitro RNAP2-dependent run off assay to measure the de novo transcription in vitro 41 . The HeLaScribe DNA template was incubated with nuclear extracts from the isogenic DU145 cells expressing Dox-inducible RBX1 shRNAs, and a transcription reaction without nucleoside triphosphates served as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the uniquely designed primers have been used to solve the problem; our data indicate that the primers successfully detect low levels of RNA transcript by primer extension and qPCR. Our novel method is distinct from those published recently [ 14 , 17 ] and displays high sensitivity, simplicity and low cost. The method will therefore benefit numerous laboratories that need in vitro transcription analysis but cannot easily employ approaches that use radioactive isotopes.…”
Section: Resultsmentioning
confidence: 93%
“…We initially sought to use a similar method to analyze transcription of the E4 reporter vector; however, we were not able to achieve stable results, although the DNA template in our experiment was depleted to a similar level [ 14 ]; it is likely that this is due to the low efficiency of transcription for E4 and ML reporter vectors. Voss et al [ 17 ] have recently reported another approach that can directly detect RNA transcripts in vitro using AffimetricsQuantigene techniques, but it relies on specialist and facilities to complete the experiment. In our study, the uniquely designed primers have been used to solve the problem; our data indicate that the primers successfully detect low levels of RNA transcript by primer extension and qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…As in other eukaryotes, the RNA Pol II-mediated transcription in C. elegans depends on the binding of transcription factors to specific gene cis-acting sequences [29]. One of the DNA substrates used in our in vitro system is HNDNA, which contains the CMV promoter and other minimal elements required to induce transcription using nuclear extract from mammalian cells [15]. Its core promoter contains all five elements (or similar sequences) typical for C. elegans and was able to induce transcription appropriately with nematode nuclear extract.…”
Section: Discussionmentioning
confidence: 99%